Testing the validity of economic growth theories using copula-based seemingly unrelated quantile kink regression - Pathairat Pastpipatkul (2018)
© Springer International Publishing AG 2017. The distinct points of view about factors driving economic growth are introduced all the time in which some effectively useful suggestions then become the growth theories, which in turn lead to various researches on economic growth. This paper aims to examine the joint validity of the growth theories using our introduced model named copula based seemingly unrelated quantile kink regression as a key tool in this work. We concentrate exclusively on the experience of Thailand and found that the growth models can prove their validities for the Thai economy through this experiment.